An overview of nitrogen oxides emissions from biomass combustion for domestic heat production. (January 2021) - Ozgen, S.; Cernuschi, S.; Caserini, S.
Abstract: In order to fulfill the European Union's climate and energy goals, the heating and cooling sector must cut its use of fossil fuels. Solid biomass can constitute an alternative to fossil fuels as a renewable and carbon-neutral source of energy but there are some aspects to biomass combustion in small-scale domestic appliances that can compromise the environmental sustainability of this renewable energy source in terms of burden on air quality. The priority pollutants in this respect are particulate matter and nitrogen oxides. While particulate matter emissions are often discussed, nitrogen oxides emissions from domestic heating appliances are relatively less in the center of attention. The aim of the present study is to review the literature regarding the nitrogen oxides emissions from this emission source discussing the main formation mechanisms and the state-of-the-art control techniques, as well as the influence of fuel composition (especially fuel bound nitrogen), heating appliance type and operating conditions with the help of the gathered experimental emission factors data. The review crosslinks several aspects usually treated separately in scientific papers (e.g., only laboratory tests with basic theory or only field tests on emission levels etc.), providing thus a quick reference tool to the state-of-the-art knowledge on this topic. Highlights: Nitrogen oxides emissions from the fuel bound nitrogen during biomass combustion. Average emission factors in the range of 63–72 mg/MJ for woody biomass combustion. Hard times for market introduction of nitrogen-rich alternative solid biofuels. Research need on residential-scale technologies for nitrogen oxides abatement.